Hohenbergia ymboreorum (Bromeliaceae): a new green-flowered bromeliad from Bahia, Brazil - Cavalcante, Brayan Paiva; Aona, Lidyanne Yuriko Saleme; Souza, Everton Hilo De (Phytotaxa, 2022)
The authors describe Hohenbergia ymboreorum, a new green-flowered species of Bromeliaceae from Bahia state. The new species was found growing in the municipality of Vitoria da Conquista as a terrestrial in a highland transitional area between Atlantic Forest and Caatinga vegetation. This new species is morphologically related to H. minor and H. augusta, but can be easily distinguished by its sparsely white-lanate inflorescence indument, longer and narrower leaves, smaller flowers, with golden-brown floral bracts not hiding the sepals, and the erect petals. Additionally, the conservation status and phenology are discussed, and a table for morphological comparison with the similar taxa is provided.